Lyophilic polyolefin master batch as well as preparation method and application thereof

By scientifically proportioning and designing the network structure of hydrophilic polyolefin masterbatch, the problem of poor hydrophilicity of polyolefin separators has been solved, improving battery performance and safety, simplifying the production process, and reducing costs.

CN121086404APending Publication Date: 2025-12-09NINGBO NENGZHIGUANG NEW MATERIALS TECH

Patent Information

Application Number
CN202511400651.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-28
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Traditional polyolefin separators are highly hydrophobic and have poor affinity with polar electrolytes, which affects ion transport, leading to battery performance degradation and safety hazards. Existing modification methods are complex, costly, or affect mechanical properties.

Method used

Using hydrophilic polyolefin masterbatch, a three-dimensional ion-driven network structure is formed by scientifically proportioning polyolefin, modified polyolefin, crosslinking agent and compatibilizer. Covalent bonds anchor hydrophilic segments, and the interface stabilization effect protects the matrix, thus constructing a covalent and ion crosslinking network to improve the hydrophilicity and mechanical properties of the membrane.

Benefits of technology

It achieves a balance between the high hydrophilicity, good mechanical properties and processing performance of polyolefin separators, improves electrolyte absorption rate and ion conduction efficiency, extends battery cycle life, and reduces production costs and complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121086404A_ABST
    Figure CN121086404A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of material science and electrochemical energy, and provides a lyophilic polyolefin master batch and a preparation method and application thereof.The lyophilic polyolefin master batch is prepared from polyolefin, modified polyolefin, a cross-linking agent and a compatilizer, the modified polyolefin comprises polyolefin grafted with polar functional groups, and the cross-linking agent comprises a cross-linking agent and a compatilizer; the polar functional group can be selected from one or more of carboxyl, hydroxyl, amido, epoxy group, anhydride group, sulfonic acid group, cyano group and ether group, and the technical problem of poor lyophilic property of the polyolefin diaphragm is creatively solved by scientifically proportioning and compounding the modified polyolefin with the polar functional group, the common polyolefin, the cross-linking agent and the compatilizer. The components in the material system have a synergistic effect: the modified polyolefin provides lyophilic property, the cross-linking agent prevents the product from being degraded, the compatilizer improves the compatibility of the components and improves the polarity, and the comprehensive improvement of the performance of the diaphragm is realized through the combined effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of materials science and electrochemical energy technology, and particularly relates to a hydrophilic polyolefin masterbatch, its preparation method and application. Background Technology

[0002] With the rapid development of portable electronic devices, electric vehicles, and energy storage systems, high-performance secondary ion batteries have become an indispensable part of modern society. As one of the key components of secondary ion batteries, the separator not only isolates the positive and negative electrodes to prevent short circuits, but also needs to have good ion conductivity to ensure the battery's efficient operation and long-term stability.

[0003] Traditional secondary ion-ion battery separators are primarily made of polyolefin materials (such as polyethylene and polypropylene). These materials possess excellent mechanical properties, chemical stability, and electrochemical stability, but they have a significant drawback: strong hydrophobicity and poor affinity for polar electrolytes. This inherent characteristic makes it difficult for the electrolyte to wet the separator, affecting the rapid and efficient transport of ions, thus limiting the battery's cycle performance, rate performance, and low-temperature performance. Especially under high-rate charge and discharge conditions, the obstructed ion transport can easily lead to accelerated battery performance degradation and even safety hazards.

[0004] Currently, the main methods for improving the hydrophilicity of polyolefin membranes are as follows: 1. Surface Coating Method: A layer of hydrophilic material, such as polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), or boehmite (γ-AlOOH), is coated onto the surface of the separator. For example, Chinese patent CN119275486A discloses a separator coated with a polymer. While this method effectively improves the hydrophilicity of the separator, it increases the separator thickness (typically by 1-4 μm), reduces porosity, and increases ion transport resistance. Furthermore, the coating may peel off during long-term battery use, affecting battery safety and long-term stability. In addition, the coating process is complex, increasing production costs.

[0005] 2. Ionizing Radiation-Assisted Grafting: This method involves grafting hydrophilic groups onto the polyolefin molecular chain using ionizing radiation. For example, Chinese patent CN116826307A discloses a technique for grafting and modifying membranes using ultraviolet light irradiation, while patent CN117673650A describes irradiation grafting to attach hydrophilic monomers with hydrophilic functional groups to the surface and / or pores of the membrane substrate. While this method provides long-lasting results, it is complex, costly, and prone to causing degradation of the polyolefin backbone, affecting the mechanical properties of the membrane.

[0006] 3. Inorganic filler addition method: Adding hydrophilic inorganic fillers, such as SiO2, Al2O3, TiO2, ZrO2, etc., to polyolefins. For example, Chinese patent CN 103059375B discloses a composite separator containing hydrophilic modified alumina nanoparticles. Although this method can improve hydrophilicity, the inorganic fillers are prone to agglomeration and difficult to disperse, and will reduce the mechanical strength and flexibility of the separator. When the content of inorganic fillers reaches an effective modification level (usually above 10wt%), the tensile strength and elongation at break of the separator will decrease significantly, which is detrimental to the long-term safety of the battery.

[0007] While the aforementioned methods have addressed the issue of poor hydrophilicity in polyolefin separators to some extent, they all possess significant limitations and drawbacks, making it difficult to simultaneously meet the requirements of battery performance, processing performance, and cost control. In particular, these methods often achieve improved hydrophilicity by adding extra process steps or introducing heterogeneous materials, which not only increases production complexity and cost but may also introduce new material interfaces, leading to new performance and safety hazards. Patent CN104733676B discloses a method for preparing a lithium-ion battery polyolefin separator, modifying the polyolefin material through extrusion of a hydrophilic prepolymer with polyolefin, followed by casting and stretching to obtain a hydrophilic polyolefin microporous separator for lithium batteries. Although this method can produce a hydrophilic separator, the production process is relatively complex, requiring the use of organic solvents such as N,N-dimethylformamide to produce the prepolymer, which is time-consuming (12 hours). Furthermore, to achieve good modification effects, the two ends of the prepolymer must be 1,1-disubstituted aromatic olefins, resulting in poor formulation versatility.

[0008] Therefore, developing a new technology that can effectively improve the hydrophilicity of polyolefin separators while maintaining their mechanical and processing properties, and that is simple and inexpensive, is a technical problem that urgently needs to be solved in the current battery separator field, and has important theoretical significance and practical application value. Summary of the Invention

[0009] This invention provides a hydrophilic polyolefin masterbatch, its preparation method, and its application, aiming to solve the above-mentioned problems.

[0010] The present invention is achieved as follows: a hydrophilic polyolefin masterbatch comprising the following raw materials in the following mass percentages: 40-80% polyolefin, 10-40% modified polyolefin, 0.5-5% crosslinking agent, and 2-15% compatibilizer.

[0011] Preferably, it comprises the following raw materials in weight percentages: 50-70% polyolefin, 20-35% modified polyolefin, 1-3% crosslinking agent, and 5-15% compatibilizer.

[0012] Preferably, it comprises the following raw materials in weight percentages: 60% polyolefin, 28% modified polyolefin, 2% crosslinking agent, and 10% compatibilizer.

[0013] Preferably, the polyolefin may be selected from one or more of ultra-high molecular weight polyethylene, high-density polyethylene, isotactic polypropylene, atactic polypropylene, and ethylene-propylene copolymer.

[0014] Preferably, the polyolefin is isotactic polypropylene (stereoregularity > 98%) or ultra-high molecular weight polyethylene (viscosity-average molecular weight (Mv) > 10. 6 g / mol).

[0015] Preferably, the modified polyolefin comprises a polyolefin grafted with polar functional groups, wherein the polar functional groups are selected from one or more of carboxyl, hydroxyl, amide, epoxy, acid anhydride, sulfonic acid, cyano, and ether groups.

[0016] Preferably, the modified polyolefin may be selected from one or more of maleic anhydride-grafted polyethylene, maleic anhydride-grafted polypropylene, acrylic acid-grafted polyethylene, acrylic acid-grafted polypropylene, methacrylic acid-grafted polyethylene, methacrylic acid-grafted polypropylene, epoxy-grafted polyethylene, and epoxy-grafted polypropylene.

[0017] Preferably, the modified polyolefin is maleic anhydride-grafted polyethylene or maleic anhydride-grafted polypropylene with a grafting rate of 0.5-5 wt%, ensuring a balance between polarity enhancement and processing performance.

[0018] Preferably, the crosslinking agent may be selected from one or more of organic peroxides, azo compounds, silane compounds, and polyfunctional monomers.

[0019] Preferably, the organic peroxide is selected from one or more of dicumyl peroxide, di-tert-butyl peroxide, benzoyl peroxide, dicumyl peroxide, di-tert-butyl hydroperoxide, and tert-butyl peroxybenzoate; the azo compound is selected from one or more of azobisisobutyronitrile, azobisisovalerate, and azobiscyclohexanenitrile; and the polyfunctional monomer is selected from one or more of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, and pentaerythritol tetraacrylate.

[0020] Preferably, the crosslinking agent is dicumyl peroxide or azobisisobutyronitrile. The crosslinking agent mainly functions to crosslink the masterbatch, preventing degradation of the masterbatch during production and ensuring the product has a suitable melt index. Preferably, the compatibilizer may be selected from one or more of polyethylene glycol, polypropylene glycol, polyethylene oxide, polypropylene oxide, polyvinylpyrrolidone, polyvinyl alcohol, block copolymers, and graft copolymers.

[0021] Preferably, the block copolymer may be selected from one or more of polyethylene-polyethylene glycol block copolymers, polypropylene-polyethylene glycol block copolymers, polyethylene-polypropylene glycol block copolymers, and polyethylene-polyethylene oxide block copolymers.

[0022] Preferably, the compatibilizer is polyethylene glycol or a polyethylene-polyethylene glycol block copolymer with a number average molecular weight (Mn) of 1000-5000. The compatibilizer's function is to ensure more uniform dispersion and mixing of the raw materials, and to form a three-dimensional ion-driven network structure without reducing the mechanical properties of the plastic. Furthermore, the polar functional groups in the compatibilizer can further enhance the product's hydrophilicity.

[0023] Preferably, the masterbatch further includes an ionic crosslinking agent comprising 0.1%-2.0% of the total mass of the masterbatch. The ionic crosslinking agent is a multifunctional monomer containing ionic groups, preferably one or more of zinc acrylate, zinc methacrylate, magnesium acrylate, and magnesium methacrylate.

[0024] This invention also provides a method for preparing a hydrophilic polyolefin masterbatch, comprising the following steps: (1) Mix the polyolefin, modified polyolefin, crosslinking agent and compatibilizer evenly. The mixing method can be mechanical mixing (equipment includes high-speed mixers such as SHR series, ribbon mixers, plow mixers, suitable for different batch quantities) or melt mixing (equipment is internal mixer, melt mixing conditions: 180-190℃, 50-80rpm, first mix polyolefin, modified polyolefin and compatibilizer for 10-15 minutes, then add crosslinking agent and mix for 3-5 minutes), mixing time 5-30 minutes). (2) The mixture obtained in step (1) is fed into an extruder and extruded and granulated at a temperature of 120-250℃ (which can be set according to the specific type of polyolefin) with a screw speed of 50-200 rpm to obtain a hydrophilic polyolefin masterbatch.

[0025] Preferably, in step (1), a high-speed mixer is used for mixing, the mixing time is 10-20 minutes, and the mixing speed is 450-700 rpm (adjusted according to the viscosity of the material, with a higher speed for low viscosity materials); in step (2), a twin-screw extruder is used for extrusion, the extrusion temperature is 160-220℃, and the screw speed is 100-150 rpm.

[0026] The present invention also provides the application of the above-mentioned hydrophilic polyolefin masterbatch in secondary ion battery separators. The hydrophilic polyolefin masterbatch and polyolefin substrate are mixed at a mass ratio of 1:5-1:20, and the secondary ion battery separator is prepared by casting and stretching processes.

[0027] The core of this invention lies in constructing a "synergistic reaction system," which forms a "three-dimensional ion dispersion network structure" through the interaction of its components. The specific principle is as follows: Covalent anchoring of hydrophilic segments: At extrusion temperatures of 180-250℃, the maleic anhydride groups on the modified polyolefin undergo ring-opening esterification with the hydroxyl groups (-OH) at the end of the compatibilizer (such as polyethylene glycol). By forming covalent ester bonds, the hydrophilic PEG segments are firmly "anchored" to the molecular chain of the modified polyolefin, avoiding the problem of easy migration and exudation of plasticizers or hydrophilic additives in traditional physical blending, which leads to performance degradation over time.

[0028] Interfacial stabilization protects the matrix: The interfacial region formed by compatibilizers (such as polyethylene glycol PEG) and modified polyolefins (such as PP-g-MAH) in the matrix, due to its high concentration of polar groups and active sites, becomes a "free radical trap" or "reaction priority region." Free radicals generated by crosslinking agents may be preferentially consumed at grafting sites that promote the reaction between MAH and PEG, or induce local crosslinking in the interfacial region, rather than indiscriminately attacking the entire PP matrix. This "interfacial stabilization" effect "locks" destructive free radical reactions onto beneficial interfacial modifications, thereby protecting the integrity of the main PP chain. This is a highly non-obvious synergistic effect; the presence of polar components and compatibilizers alters the action mode of crosslinking agents on the PP matrix, transforming them from primary "degrading agents" to effective "stabilizers," simultaneously achieving a balance between hydrophilicity and mechanical properties.

[0029] The introduction of ionic crosslinking agents, working synergistically with primary crosslinking agents (such as peroxides), can construct a dual-network structure in polyolefin matrices, where both covalent and ionic crosslinking networks coexist. The covalent crosslinking network provides a permanent and stable mechanical framework; while the ion clusters in the ionic crosslinking network (such as ion pairs formed by zinc and magnesium salts) undergo reversible breakage and recombination under heat or shear stress (dynamic crosslinking-decrosslinking behavior). This dynamic network not only allows for moderate decrosslinking during processing (under high-temperature shearing), improving flowability, but also effectively dissipates stress generated during charging and discharging, enhancing the membrane's toughness and fatigue resistance, thus potentially significantly extending battery cycle life. Simultaneously, the introduced metal ions (such as Zn...) 2+ It itself has a certain promoting effect on lithium ion transport in electrolyte.

[0030] Compared with the prior art, the embodiments of this application have the following main advantages: 1. This invention creatively solves the technical problem of poor hydrophilicity in polyolefin membranes by scientifically proportioning and compounding modified polyolefins with polar functional groups with ordinary polyolefins, crosslinking agents, and compatibilizers. There is a synergistic effect among the components in the material system: the modified polyolefins provide hydrophilicity, the crosslinking agents prevent product degradation, and the compatibilizers improve component compatibility and enhance polarity, working together to achieve a comprehensive improvement in membrane performance.

[0031] 2. The masterbatch can be directly used in existing polyolefin membrane production lines without the need for additional equipment; the preparation process is solvent-free, making it more environmentally friendly, and the polyolefin content can reach up to 90%, resulting in low cost and easy industrialization.

[0032] 3. This invention does not use inorganic fillers, therefore it does not affect the mechanical and processing properties of the diaphragm, and avoids problems such as filler agglomeration.

[0033] 4. This invention uses the masterbatch method, which avoids the surface coating process, does not increase the thickness of the separator, does not affect the porosity, and is conducive to maintaining the high energy density of the battery.

[0034] 5. The separator prepared by the masterbatch of the present invention has good hydrophilicity, which can significantly improve the absorption rate and ion conduction efficiency of the electrolyte, thereby improving the cycle performance and rate performance of the battery. Attached Figure Description

[0035] Figure 1 This is a flowchart of a method for preparing a hydrophilic polyolefin masterbatch provided by the present invention. Detailed Implementation

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein in the specification of the application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application; the terms "comprising" and "having," and any variations thereof, in the specification, claims, and foregoing drawings of this application are intended to cover non-exclusive inclusion. The terms "first," "second," etc., in the specification, claims, or foregoing drawings of this application are used to distinguish different objects, not to describe a particular order.

[0037] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0038] Example 1 This invention provides a hydrophilic polyolefin masterbatch, such as... Figure 1 As shown, the preparation method steps are as follows: Ultra-high molecular weight polypropylene (isotactic index 99%), maleic anhydride-grafted polypropylene (grafting rate 2wt%), azobisisobutyronitrile, and polypropylene-polyethylene glycol block copolymer were mixed in a high-speed mixer at a mass ratio of 80:14:1:5 for 15 minutes at a mixing speed of 600 rpm. The uniformly mixed material is then fed into a twin-screw extruder at an extrusion temperature of 220°C and a screw speed of 300 rpm. After underwater strand granulation, a hydrophilic polyolefin masterbatch is obtained.

[0039] Example 2 Same as Example 1, except that the raw material is ultra-high molecular weight polyethylene (Mv=3×10). 6 The mixture consisted of g / mol of maleic anhydride-grafted polyethylene (grafting rate 1.5wt%), azobisisobutyronitrile, and polyethylene-polyethylene glycol block copolymer in a mass ratio of 70:20:2:8; the mixing time was 20 minutes; the extrusion temperature was 200°C and the screw speed was 150 rpm.

[0040] Example 3 Similar to Example 1, except that the raw materials are polypropylene (isotactic index 98.5%), maleic anhydride-grafted polypropylene (grafting rate 3wt%), di-tert-butyl peroxide, and polyethylene glycol in a mass ratio of 60:30:1.5:8.5; the mixing speed is 450 rpm; the extrusion temperature is 190°C; and the screw speed is 120 rpm.

[0041] Example 4 Same as Example 1, except that the raw material is ultra-high molecular weight polyethylene (Mv=2×10). 6 The mixture consisted of propylene glycol (g / mol), acrylic acid-grafted polypropylene (grafting rate 2wt%), dicumyl peroxide, and polypropylene glycol in a mass ratio of 55:32:2.5:10.5; the mixing time was 18 minutes and the mixing speed was 550 rpm; extrusion was performed using a single-screw extruder at an extrusion temperature of 190°C and a screw speed of 100 rpm.

[0042] Example 5 Similar to Example 1, except that: the raw materials are polypropylene (isotactic index 99%), maleic anhydride-grafted polypropylene (grafting rate 1.5wt%), trimethylolpropane triacrylate, and polyvinylpyrrolidone, with a mass ratio of 50:35:3:12; the mixing time is 25 minutes, the mixing speed is 700 rpm; the extrusion temperature is 200°C, and the screw speed is 180 rpm.

[0043] Example 6 Same as Example 1, except that the raw material is ultra-high molecular weight polyethylene (Mv=5×10). 6The mixture consisted of g / mol of maleic anhydride-grafted polyethylene (grafting rate 2wt%), azobisisobutyronitrile and polyethylene-polyethylene glycol block copolymer with a molecular weight of 2000, in a mass ratio of 70:25:2:3; the mixing time was 20 minutes; the extrusion temperature was 190℃ and the screw speed was 120 rpm; the granulation method was water-cooled pelletizing.

[0044] Example 7 Similar to Example 1, except that the preparation method is melt mixing; the raw materials are polypropylene (isotactic index 98.5%), acrylic acid-grafted polypropylene (grafting rate 3wt%), dicumyl peroxide and polyethylene glycol (molecular weight 4000), with a mass ratio of 60:30:1.5:8.5; first, the polypropylene, acrylic acid-grafted polypropylene and polyethylene glycol are mixed in a mixer at 190°C for 10 minutes, and then dicumyl peroxide is added and mixed for 5 minutes; granulation is performed by extrusion at 190°C using a single screw extruder.

[0045] Example 8 Same as Example 1, except that the raw material is ultra-high molecular weight polyethylene (Mv=3×10). 6 The mixture consisted of g / mol of epoxy-grafted polyethylene (grafting rate 2.5wt%), trimethylolpropane triacrylate, and polyvinylpyrrolidone in a mass ratio of 50:35:3:12; the mixing time was 10 minutes, the mixing speed was 450 rpm, the extrusion temperature was 200℃, and the screw speed was 180 rpm.

[0046] Example 9 (Based on Example 1, with the addition of an ionic crosslinking agent) Ultra-high molecular weight polypropylene, maleic anhydride-grafted polypropylene, azobisisobutyronitrile (AIBN), polypropylene-polyethylene glycol block copolymer, and zinc methacrylate (ZDMA) were mixed in a high-speed mixer at a mass ratio of 80:14:1:5:0.1 for 15 minutes at a mixing speed of 600 rpm. The homogeneous mixture was then fed into a twin-screw extruder at an extrusion temperature of 220°C and a screw speed of 300 rpm. After underwater strand granulation, a hydrophilic polyolefin masterbatch was obtained.

[0047] Example 10 (Based on Example 1, with the addition of an ionic crosslinking agent) The difference from Example 1 is that the raw materials are ultra-high molecular weight polypropylene, maleic anhydride-grafted polypropylene, azobisisobutyronitrile, polypropylene-polyethylene glycol block copolymer, and zinc methacrylate (ZDMA) in a mass ratio of 80:14:1:5:1.0.

[0048] Example 11 (Based on Example 1, with the addition of an ionic crosslinking agent) The difference from Example 1 is that the raw materials are ultra-high molecular weight polypropylene, maleic anhydride-grafted polypropylene, azobisisobutyronitrile, polypropylene-polyethylene glycol block copolymer, and zinc methacrylate (ZDMA) in a mass ratio of 80:14:1:5:2.0.

[0049] Comparative Example 1 Same as Example 1, except that the raw material is polypropylene and no modifying components are added.

[0050] Comparative Example 2 Similar to Example 1, except that the raw materials are polypropylene and maleic anhydride-grafted polypropylene in a mass ratio of 90:10, and no azobisisobutyronitrile (crosslinking agent) and polypropylene-polyethylene glycol block copolymer (compatibility agent) are added.

[0051] Comparative Example 3 Similar to Example 1, except that the raw materials are polypropylene, dicumyl peroxide, and polyethylene glycol in a mass ratio of 85:1:14, and no modified polyolefin is added.

[0052] Comparative Example 4 Similar to Example 1, except that the raw materials are polypropylene, maleic anhydride-grafted polyethylene, and polyethylene glycol in a mass ratio of 81:14:5, and no crosslinking agent is added.

[0053] Comparative Example 5 Similar to Example 1, except that the raw materials are polypropylene, maleic anhydride-grafted polyethylene, and dicumyl peroxide in a mass ratio of 85:14:1, and no compatibilizer is added.

[0054] Comparative Example 6 The difference from Example 9 is that the mass ratio of ultra-high molecular weight polypropylene, maleic anhydride-grafted polypropylene, azobisisobutyronitrile, polypropylene-polyethylene glycol block copolymer, and zinc methacrylate (ZDMA) is 80:14:1:5:3.

[0055] Comparative Example 7 The difference from Example 9 is that the mass ratio of ultra-high molecular weight polypropylene, maleic anhydride-grafted polypropylene, azobisisobutyronitrile, polypropylene-polyethylene glycol block copolymer, and zinc methacrylate (ZDMA) is 80:14:1:5:0.05.

[0056] Performance Tests and Results I. Test methods for hydrophilic polyolefin masterbatches (based on industry-standard guidelines): Melt flow index: According to GB / T 3682.1-2018, the test conditions for polyethylene are 190℃ / 2.16kg, and for polypropylene are 230℃ / 2.16kg. The instrument is a ZRZ1452 melt flow rate meter. Surface dyne value: According to GB / T 14216-2020, BYK Gardner 28-40mN / m series dyne test pen was used; Contact angle: According to GB / T 24368-2009, the seat drop method is adopted, the test solution is distilled water at 25℃, and the instrument is a JC2000D1 contact angle measuring instrument; Tensile strength: According to GB / T 1040.3-2006, the test rate is 50 mm / min, and the instrument is a CMT6104 electronic universal testing machine.

[0057] The masterbatch obtained from the above embodiments and the masterbatch obtained from the comparative example were subjected to various performance tests. The performance test results are detailed in Table 1.

[0058] Table 1. Test Results of Masterbatch Performance

[0059] The results above show that: Significantly improved hydrophilicity: The surface dyne values ​​of Examples 1 to 8 all reached over 38 dyne / cm, far exceeding the 28 dyne / cm of unmodified polyolefin (Comparative Example 1). The contact angle with water was also significantly reduced to 78°, while that of unmodified PP was as high as 110°. This strongly demonstrates that the present invention successfully modifies polyolefins from a hydrophobic surface to a hydrophilic surface. The improvement in hydrophilicity in Comparative Examples 2, 3, and 4 was not significant, indicating that stable and uniform surface polarization cannot be achieved without any of the polar components, crosslinking agents, or compatibilizers.

[0060] Processing performance remained good: the melt flow index (MFI) of Examples 1 to 8 was controlled at a low level (<1 g / 10 min), indicating that the crosslinking agent successfully inhibited the degradation of the polymer during high-temperature extrusion, ensuring that the material had suitable melt viscosity and good processing stability. In contrast, Comparative Examples 2 and 4, which lacked crosslinking agents, had MFI values ​​that soared to an uncontrollable >1.2 g / 10 min, which directly proved that the polymer chains had broken severely, and the material could no longer be processed and molded normally.

[0061] Good mechanical properties were maintained: The membranes prepared in Examples 1 to 8 all maintained excellent mechanical properties, with tensile strengths all above 100 MPa, meeting the strength requirements of battery separators and demonstrating the compatibility of the formulation with high-strength substrates. In contrast, Comparative Examples 2 and 4, which degraded, showed a significant decrease in tensile strength, became brittle, and had a significantly reduced elongation at break, failing to guarantee the integrity of the separator during battery winding and long-term use.

[0062] Examples 9 to 11 introduce specific amounts of ionic crosslinking agents into the basic four-component system, successfully constructing a dual network structure in which both "covalent crosslinking network" and "ionic crosslinking network" coexist. While maintaining excellent hydrophilicity and processability, this significantly improves the toughness, thermal stability and battery cycle life of the separator.

[0063] II. Battery Performance Testing Methods and Standards 1. Diaphragm preparation The masterbatches prepared in each embodiment and comparative example were processed into microporous membranes with a thickness of 20±2μm through melt extrusion, casting, and biaxial stretching (longitudinal stretching ratio: 5:1, transverse stretching ratio: 8:1). The porosity of all membranes was controlled between 40% and 45% to ensure the consistency of the basic structure.

[0064] 2. Battery assembly (CR2032 button cell) Positive electrode: LiFePO4 (LFP), conductive carbon black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 8:1:1 and coated onto aluminum foil.

[0065] Negative electrode: Lithium metal sheet.

[0066] Electrolyte: 1M LiPF6 in EC / DEC / EMC (volume ratio 1:1:1), with 2% VC added.

[0067] Assembly environment: Glove box with dew point below -40°C.

[0068] 3. Test Methods and Standards Ionic conductivity: Method: After immersing the diaphragm in the electrolyte for 24 hours, a symmetrical SS|diaphragm|SS (SS is a stainless steel blocking electrode) cell was assembled.

[0069] Equipment: Electrochemical workstation (such as Solartron 1260).

[0070] Standard: Measured by electrochemical impedance spectroscopy (EIS) in the frequency range of 100 kHz to 0.1 Hz. The formula for calculating ionic conductivity is σ = d / (R_b × A), where d is the membrane thickness, R_b is the bulk resistance (obtained from the intercept of the high-frequency region of the impedance spectrum and the real axis), and A is the membrane area (1.767 cm², corresponding to a diameter of 15 mm).

[0071] Cycle Performance: Method: Charge-discharge cycle test was performed at 0.5C rate (voltage range: 2.5-4.2V vs. Li+ / Li).

[0072] Equipment: Blue Battery Testing System.

[0073] Standard: Record the discharge specific capacity of the 1st, 300th and 500th cycles, and calculate the capacity retention rate = (discharge capacity of the Nth cycle / discharge capacity of the 1st cycle) × 100%.

[0074] Rate Capability: Method: Discharge was performed at rates of 0.2C, 0.5C, 1C, 2C, and 5C, with each rate cycled 5 times, and finally returned to the 0.2C rate.

[0075] Standard: Calculate the rate capacity retention at each high rate (e.g., 5C) = (high rate discharge capacity / average of initial discharge capacity at 0.2C) × 100%.

[0076] Low-Temperature Performance: Method: Discharge was performed at a rate of 0.2C in an ambient chamber at -20℃.

[0077] Standard: Calculate Low-Temp Capacity Retention = (Discharge Capacity at -20℃ / Discharge Capacity at 25℃) × 100%.

[0078] The test results are shown in Table 2 below: Table 2 Battery Performance Test Results

[0079] The results above show that this invention not only improves the material properties of the masterbatch, but more importantly, when applied to secondary ion battery separators, it can bring about a comprehensive improvement in ionic conductivity, cycle life, rate performance, and low-temperature performance.

[0080] It should be noted that, for the sake of simplicity, the foregoing embodiments are all described as a series of actions. However, those skilled in the art should understand that the present invention is not limited to the described order of actions, as some steps may be performed in other orders or simultaneously according to the present invention. Furthermore, those skilled in the art should also understand that the embodiments described in the specification are preferred embodiments, and the actions and modules involved are not necessarily essential to the present invention.

[0081] It should be understood that the disclosed apparatus can be implemented in other ways, as illustrated in the embodiments provided in this application. For example, the apparatus embodiments described above are merely illustrative; the division of units described above is only a logical functional division, and in actual implementation, there may be other division methods. For example, multiple units or components may be combined or integrated into another system, or some features may be ignored or not executed. Furthermore, the coupling or communication connections shown or discussed may be through some interfaces; the indirect coupling or communication connections between devices or units may be telecommunications or other forms.

[0082] The units described above as separate components may or may not be physically separate. The components shown as units may or may not be physical units; that is, they may be located in one place or distributed across multiple network units. Some or all of the units can be selected to achieve the purpose of this embodiment according to actual needs.

[0083] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on these embodiments, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still combine, add, delete, or otherwise adjust the features of the various embodiments of the present invention according to the circumstances without conflict or creative effort, thereby obtaining different technical solutions that do not fundamentally depart from the concept of the present invention. These technical solutions also fall within the scope of protection of the present invention.

Claims

1. A hydrophilic polyolefin masterbatch, characterized in that, It includes the following raw materials in weight percentage: 40-80% polyolefin, 10-40% modified polyolefin, 0.5-5% crosslinking agent, and 2-15% compatibilizer.

2. The hydrophilic polyolefin masterbatch as described in claim 1, characterized in that, It includes the following raw materials by weight percentage: 50-70% polyolefin, 20-35% modified polyolefin, 1-3% crosslinking agent, and 5-15% compatibilizer.

3. The hydrophilic polyolefin masterbatch as described in claim 2, characterized in that, The polyolefin includes one or more of ultra-high molecular weight polyethylene, high-density polyethylene, isotactic polypropylene, atactic polypropylene, and ethylene-propylene copolymer.

4. The hydrophilic polyolefin masterbatch as described in claim 1, characterized in that, The modified polyolefin includes a polyolefin grafted with polar functional groups, wherein the polar functional groups include one or more of carboxyl, hydroxyl, amide, epoxy, acid anhydride, sulfonic acid, cyano, and ether groups.

5. The hydrophilic polyolefin masterbatch as described in claim 4, characterized in that, The grafting rate of the modified polyolefin is 0.5-5 wt%.

6. The hydrophilic polyolefin masterbatch as described in claim 1, characterized in that, The crosslinking agent includes one or more of organic peroxides, azo compounds, silane compounds, and polyfunctional monomers.

7. The hydrophilic polyolefin masterbatch as described in claim 1, characterized in that, The compatibilizer includes one or more of polyethylene glycol, polypropylene glycol, polyethylene oxide, polypropylene oxide, polyvinylpyrrolidone, polyvinyl alcohol, block copolymers, and graft copolymers.

8. The hydrophilic polyolefin masterbatch as described in claim 1, characterized in that, It also includes 0.1%-2.0% of an ionic crosslinking agent by weight of the total masterbatch, wherein the ionic crosslinking agent is a multifunctional monomer containing ionic groups.

9. The method for preparing the hydrophilic polyolefin masterbatch according to any one of claims 1-8, characterized in that, Includes the following steps: (1) Mix the polyolefin, modified polyolefin, crosslinking agent and compatibilizer evenly; (2) Extrude the mixture at 120-250℃ to granulate.

10. The application of the hydrophilic polyolefin masterbatch as described in any one of claims 1-8 or the hydrophilic polyolefin masterbatch prepared by the method of claim 9 in the separator of a secondary ion battery.

Citation Information

Patent Citations

  • Lithium-ion battery diaphragm master batch and preparation method thereof

    CN103059375B

  • A method for preparing a polyolefin microporous membrane for lithium-ion batteries

    CN104733676B

  • Lyophilic lithium battery diaphragm and preparation method thereof

    CN116826307A

  • Battery diaphragm and battery

    CN119275486A

Cited By

  • High-oxidation-resistance and high-weather-resistance battery diaphragm and preparation method thereof

    CN121769443A

  • High-oxidation-resistant and high-weather-resistant battery separator and its preparation method

    CN121769443B